A contrastive analysis of food name forming between Korea and Indonesia: a morphological study - Megasari, Jayanti; Widyana, Ashanti (Universitas Pendidikan Indonesia (UPI), 2022)
Food cannot be separated from our daily lives. The meaning of food in people's lives is to fulfil the needs of the body and other forms of culture. This study compares the formation of Korean and Indonesian food names. This study uses a descriptive research method and uses a morphological study as an analysis. The data used in this study are Korean and Indonesian food names from various relevant sources. This research was conducted as an introduction to culture through the culinary arts and as a form of developing the science of morphology. This study compares the formation and pattern used in naming Korean food names with the formation and pattern of naming Indonesian food names. This research produces formation patterns based on word categories. In Korean food, names produce 12 patterns of formation and in Indonesian food produce 5 patterns of formation.